Worktext for automotive steering, suspension, and alignment - Halderman, James D. 1943-; Mitchell, Chase D. (Prentice Hall multimedia series in automotive technology, 2000)
For courses in Automotive Steering, Suspension, and Alignment, and Automotive Chassis Systems.Today's automotive repair industry demands knowledge of diagnostic procedures and skill development as never before. Focusing primarily on problem diagnosis, this clear and concise text is packed with examples of practical technical information, ideas, tips, and detailed service techniques. Troubleshooting and typical service problems are explored throughout. Halderman and Mitchell provide all essential material but weed out extraneous topics, and the text's real-world perspective reflects their extensive practical experience.